ASPEK MORALITAS DALAM KUMPULAN CERPEN SEMPRONG PUUN KARYA NI WAYAN ANTARI DKK DAN IMPLIKASINYA DALAM PEMBELAJARAN SASTRA DI SMA - I Nyoman Astawan; I Nyoman Sadwika; I Dewa Putu Juwana (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
This study reveals the aspect of morality in the collection of short stories Semprong Puun by Ni Wayan Antari et al and its implications in learning literature. This study aims to obtain an overview of the aspects of morality contained and its implication in learning literature at Senior High School in the collection of short stories Semprong Puun by Ni Wayan Antari et al. This research uses qualitative research type. The method used in obtaining the data is the method of documentation or literature study. The results of data analysis show that some of the short stories in the collection of Semprong Puun short stories have moral values ​​such as honesty, being yourself, willingness to take responsibility, moral independence, moral courage, humility, being realistic, and critical. In their work, Ni Wayan Antari et al emphasize the value of humility as well as being realistic and critical. Based on the results of the research that has been done, it is known that the aspect of morality in the collection of short stories from Semprong Puun is relevant in learning literature in high school.